2023
DOI: 10.1021/acscentsci.2c01406
|View full text |Cite
|
Sign up to set email alerts
|

Designing Robust Superhydrophobic Materials for Inhibiting Nucleation of Clathrate Hydrates by Imitating Glass Sponges

Abstract: Superhydrophobic surfaces are suggested to deal with hydrate blockage because they can greatly reduce adhesion with the formed hydrates. However, they may promote the formation of fresh hydrate nuclei by inducing an orderly arrangement of water molecules, further aggravating hydrate blockage and meanwhile suffering from their fragile surfaces. Here, inspired by glass sponges, we report a robust anti-hydratenucleation superhydrophobic three-dimensional (3D) porous skeleton, perfectly resolving the conflict betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…109,110 The hydrophobicity of these biological surfaces, which is formed by their unique microstructures and chemical compositions, provides abundant biological samples for bioinspired surface research. 111,112 As shown in Figure 6c, Wang et al 111 found that the thin onion film obtained from peeling off an onion bulb scale exhibited low hydrate adhesion due to its porous structures and the surface cuticle layer. Further, utilizing the bioproperties of a natural onion film as a template, a hydrate-phobic surface was developed with remarkably low hydrate adhesion strength.…”
Section: ■ Hydrate Blockage Prevention and Control Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…109,110 The hydrophobicity of these biological surfaces, which is formed by their unique microstructures and chemical compositions, provides abundant biological samples for bioinspired surface research. 111,112 As shown in Figure 6c, Wang et al 111 found that the thin onion film obtained from peeling off an onion bulb scale exhibited low hydrate adhesion due to its porous structures and the surface cuticle layer. Further, utilizing the bioproperties of a natural onion film as a template, a hydrate-phobic surface was developed with remarkably low hydrate adhesion strength.…”
Section: ■ Hydrate Blockage Prevention and Control Methodsmentioning
confidence: 99%
“…Additionally, under the driving force of liquids, water droplets are scarcely deposited on hydrophobic coating surfaces via the rolling mechanism; thus, hydrophobic surfaces exhibit an antihydrate adhesion mechanism. In nature, some biological surfaces have special wetting properties, such as the hydrophobic nature of lotus leaves unsullied from mud and the unique ability of hogweed to trap insects. , The hydrophobicity of these biological surfaces, which is formed by their unique microstructures and chemical compositions, provides abundant biological samples for bioinspired surface research. , As shown in Figure c, Wang et al found that the thin onion film obtained from peeling off an onion bulb scale exhibited low hydrate adhesion due to its porous structures and the surface cuticle layer. Further, utilizing the bioproperties of a natural onion film as a template, a hydrate-phobic surface was developed with remarkably low hydrate adhesion strength.…”
Section: Hydrate Blockage Prevention and Control Methodsmentioning
confidence: 99%
“…Created by taking inspiration from natural entities such as lotus leaves and hopping insects, superhydrophobic surfaces have garnered significant attention and been extensively employed in various domains, including anticorrosion applications, anti-icing solutions, self-cleaning mechanisms, and oil–water separation techniques due to their excellent noninfiltration properties. These surfaces typically comprise a combination of micro- and nanoscale rough structures along with hydrophobic materials possessing low surface energy . Moreover, nanoparticles such as silicon carbide, silicon dioxide, titanium dioxide, and carbon nanotubes are commonly utilized in constructing the rough structures for superhydrophobic coatings, owing to their large specific surface area and favorable dispersion properties. As research on superhydrophobic surfaces advances, an increasing array of functional nanoparticles has been incorporated into these surfaces to fulfill specific properties and broaden their scope of application.…”
Section: Introductionmentioning
confidence: 99%
“…These surfaces typically comprise a combination of micro-and nanoscale rough structures along with hydrophobic materials possessing low surface energy. 40 Moreover, nanoparticles such as silicon carbide, silicon dioxide, titanium dioxide, and carbon nanotubes are commonly utilized in constructing the rough structures for superhydrophobic coatings, owing to their large specific surface area and favorable dispersion properties. 41−46 As research on superhydrophobic surfaces advances, an increasing array of functional nanoparticles has been incorporated into these surfaces to fulfill specific properties and broaden their scope of application.…”
Section: Introductionmentioning
confidence: 99%
“…While the polymer coating approach has demonstrated promising results in enhancing the puncture resistance of fabrics, there is still a challenge in developing multifunctional protective composites that can enhance the overall defensive performance of personal protective equipment beyond just puncture resistance. Numerous studies have drawn inspiration from nature and explored the applications of superhydrophobic surfaces in various fields, including corrosion prevention, , self-cleaning, and antifouling. , These surfaces typically feature micro and nano rough structures with low surface energy . Nanoparticles such as silica, titanium dioxide, , and silicon carbide are commonly utilized to enhance the mechanical strength of polymers and create the desired rough structure in superhydrophobic coatings.…”
Section: Introductionmentioning
confidence: 99%